Social Connections and Group Banking - Dean S. Karlan (Yale University, Economic Growth Center, 2005)
Lending to the poor is expensive due to high screening, monitoring, and enforcement costs. Group lending advocates believe lenders overcome this by harnessing social connections. Using data from FINCA-Peru, I exploit a quasi-random group formation process to find evidence of peers successfully monitoring and enforcing joint-liability loans. Individuals with stronger social connections to their fellow group members (i.e., either living closer or being of a similar culture) have higher repayment and higher savings. Furthermore, I observe direct evidence that relationships deteriorate after default, and that through successful monitoring, individuals know who to punish and who not to punish after default.
Keywords: O12; O16; O17; Z13; 330; Microfinance; Group lending; informal savings; social capital; Informeller Finanzsektor; Social Capital; Peru; Mikrofinanzierung; Soziale Beziehungen